2016
DOI: 10.1002/hrm.21782
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Employees’ Perceptions of their Organization's Change History Matter? The Role of Change Appraisals

Abstract: In this article, we identify employees' change history in an organization as a key antecedent of their appraisals about organizational change (i.e., threat, harm, and challenge

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 66 publications
(116 reference statements)
6
59
0
Order By: Relevance
“…g All factors combined into a single factor. ***p < 0.001 important role in influencing their reactions to change (Herold et al, 2007;Rafferty & Restubog, 2017). Specifically, we demonstrated that organizations which have developed and implemented a strong HR system create a framework that guides employees through the change.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…g All factors combined into a single factor. ***p < 0.001 important role in influencing their reactions to change (Herold et al, 2007;Rafferty & Restubog, 2017). Specifically, we demonstrated that organizations which have developed and implemented a strong HR system create a framework that guides employees through the change.…”
Section: Discussionmentioning
confidence: 74%
“…Change management research focuses on change content and change implementation to assess employee reactions toward change and identify successful change management strategies (Armenakis & Bedeian, ). Our first contribution is therefore to the small but growing number of studies that have explored change by demonstrating that the context in which employees are embedded plays an important role in influencing their reactions to change (Herold et al, ; Rafferty & Restubog, ). Specifically, we demonstrated that organizations which have developed and implemented a strong HR system create a framework that guides employees through the change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with a study by Moore et al (2004), who find support for a stress-accumulation model as employees encounter multiple downsizing events. Studies conducted by Allen, Freeman, Russell, Reizenstein, and Rentz (2001), Rafferty and Griffin (2006), and Rafferty and Restubog (2017), comes to the finding that higher scores on perceptual measures on the frequency of change lead to stronger feelings of uncertainty and increased turnover intention. Similarly, qualitative accounts of organizational change in settings such as the English NHS do suggest some degree of accumulation when reform is nearly constant (e.g., McMurray, 2010).…”
Section: Intense Reform Sequences and Organizational Absenteeism Ratesmentioning
confidence: 99%
“…Structural reforms have been found to have a large variety of intended and unintended effects on organizations, with many of the latter being related to perceptions of uncertainty that they produce (Bommer and Jalajas 1999;Amiot et al 2006;Pollitt 2007;Moore, Grunberg, and Greenberg 2004;Rafferty and Griffin 2006). Frequent changes in the makeup of an organization are accompanied by uncertainty regarding future structures, with employees wondering whether and how any changes will affect them and their position within an organization (Rafferty and Restubog 2017). As the rate of public sector restructuring increases to the point that some organizations experience it as continuous (MacCarthaigh 2012;Pollitt 2007), perceptions of uncertainty may become exacerbated due to a lack of a determinate end to the structural reform process (Rafferty and Griffin 2006;Rafferty and Restubog 2017).…”
Section: The Theoretical Link Between Structural Reforms and Defensivmentioning
confidence: 99%